The Role of Janus Kinase Inhibitors in Dermatology - Rika Desviorita; Gardenia Akhyar (Green Publisher Indonesia, 2026)
Janus kinase (JAK) is an intracellular protein of non-receptor tyrosine kinase that functions in cellular regulation and cytokine signaling, thereby producing inflammation. Inhibition of JAK with small molecules that modulate cytokines by blocking the release of Adenosine Triphosphate (ATP) for JAK phosphorylation can prevent inflammation. These molecules are known as Janus Kinase Inhibitors (JAKi). Several related studies have demonstrated that JAKi can be used in the treatment of autoimmune and neoplastic conditions both topically and systemically. Currently, JAKi has been utilized in dermatology and has obtained approval from the Food and Drug Administration (FDA), primarily for treating Atopic Dermatitis (AD), Alopecia Areata (AA), psoriasis, and vitiligo. This review examines the molecular mechanisms of JAK/STAT pathway dysregulation in inflammatory skin diseases, evaluates the efficacy and safety profiles of both topical and systemic JAKi formulations across multiple dermatological conditions, and compares their therapeutic effectiveness against conventional immunosuppressants and biologic agents. The findings indicate that JAKi demonstrates superior rapid onset of action, multi-target cytokine suppression, and favorable safety profiles in short-to-medium term use, positioning them as innovative therapeutic alternatives for patients with treatment-refractory inflammatory skin diseases.